IMPROVING THE METHODOLOGY OF ACCOUNTING FOR FINISHED PRODUCTS IN THE OIL AND GAS INDUSTRY - MAKHKAMOVA SAIDA GAIRATOVNA, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The main objective of this article is to properly organize finished goods accounting in the oil and gas industry. To achieve this goal, the following objectives were defined: studying the specifics of the oil refining production process, conducting a theoretical study of cost allocation in the oil and gas industry, and methods for allocating complex costs in oil refining, examining cost accounting and calculation objects, and properly allocating complex expenses. In this article, we will examine in detail how to properly manage finished goods accounting and determine the financial result (profit or loss) in accounting based on the regulatory documents of the Republic of Uzbekistan.